Assessment of Librarians’ Management Skills and Their Impact on Resource Development and Quality Services in Pakistani University Libraries - Sultan, Zahid; Ahmad, Shamshad (IJoLIS, 2025)
Background: This study examines how management skills in librarians can be evaluated and also how the outcome of this evaluation affects development of the resources and the quality of services at university libraries in Pakistan. Purpose: The research aim will be to establish the most essential leadership skills that generate better resource management skills and service quality results in university libraries. The present study aims at examining the existing gaps in library management and determine the relationship between these skills with library operational outcomes. Objective: To explore how the technological expertise of librarians affects their ability to operate digital resources and modernise library services. To determine the issues encountered by the librarians in the implementation of management skills in the development and service delivery of the resources. To determine how the strategic planning and leadership capabilities of librarians influence the performance of university libraries in general.. Methods: The researchers embraced quantitative research methodology with the use of survey data as the major data collection instrument. A structured questionnaire was sent online to librarians of Higher Education Commission (HEC) identified universities in the public and private sector in Pakistan. The approach was chosen to capture credible and quantifiable information so that the researchers could compare the trends, gauge management capabilities, and the effects that the management capabilities have on the development of resources and provision of quality library services. Results: Administrative competence among librarians enhances university libraries' resource development capability and their service quality delivery performance. Learning communities should have such skills in order to meet their evolving needs. Conclusion: Education programs of librarians should be implemented as a priority as they will generate personnel with increased managerial skills that will restructure their libraries to improved academic support platforms. Implications: The given study contributes to literature in library management by providing pertinent information to administrators who wish to apply the best practices to achieve improved library outcomes.